Using of geophysical methods for estimation of the technological properties of ores of pyrite-polymetallic deposits; Bulletin of the Tomsk Polytechnic University; Vol. 309, № 4 - Titov D. V. (Natural sciences, 2006)
Заглавие с титульного листа